French Cycling : A Social and Cultural History. - Dauncey, Hugh. (Contemporary French and Francophone Cultures Series, 2012)
French Cycling: a Social and Cultural History aims to provide a balanced and detailed analytical survey of the complex leisure activity, sport, and industry that is cycling in France. Identifying key events, practices, stakeholders and institutions in the history of French cycling, the volume presents an interdisciplinary analysis of how cycling has been significant in French society and culture since the late Nineteenth century. Cycling as Leisure is considered through reference to the adoption of the bicycle as an instrument of tourism and emancipation by women in the 1880s, for example, or by study of the development in the 1990s of long-distance tourist cycle routes. Cycling as Sport and its attendant dimensions of amateurism/professionalism, national identity, the body and doping, and other issues is investigated through study of the history of the Tour de France, the track-racing organised at the Vélodrome d'hiver in Paris in the 1920s and 1930s and other emblematic events. Cycling as Industry.